The Effect of Transformational Leadership Style on the Work Motivation of Samapta Unit Officers at the Central Jakarta Metropolitan Police Resort - Wira Jaya Putra Kusuma; Tugimin Supriyadi; Sandra Adetya (Journal of Health and Multidisciplinary Health Studies, 2026)
Transformational leadership plays an important role in enhancing employees' work motivation, particularly in police organizations characterized by high demands for discipline and public service. This study examined the effect of transformational leadership on the work motivation of members of the Samapta Unit at the Central Jakarta Metropolitan Police Resort. Using a quantitative explanatory design, data were collected from 166 police officers selected through simple random sampling. Transformational leadership was measured using the adapted Multifactor Leadership Questionnaire (MLQ Form 5X), while work motivation was assessed using Haq's adaptation of Herzberg's motivator factors. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and simple linear regression in JASP. The results showed that transformational leadership had a positive and significant effect on work motivation (R = 0.166, R² = 0.028, F = 4.664, p = 0.032). Although transformational leadership explained only 2.8% of the variance in work motivation, the findings suggest that strengthening transformational leadership practices may help improve police officers' work motivation.